2019
DOI: 10.1111/jre.12634
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis links to exacerbation of myocardial dysfunction in subjects with type 2 diabetes

Abstract: Background and Objective Subjects with diabetes and periodontitis are at high risk of cardiovascular events, while the subclinical alterations of cardiac function in this cohort remain unclear. This cross‐sectional study investigated the association of periodontitis with left ventricle (LV) structural and functional abnormalities in subjects with type 2 diabetes mellitus (T2DM). Material and Methods A total of 115 subjects with T2DM were divided into Control group (n = 32) with no or mild periodontitis, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
(102 reference statements)
2
14
0
Order By: Relevance
“…As shown in our recent study on patients with T2DM (Wang et al., 2019), the E/e' ratio in the subjects with no or mild periodontitis and those with severe periodontitis was 8.4 ± 1.7 (standard deviation, SD ) and 10.5 ± 2.9 ( SD ), respectively. Assuming the clinically important reduction in E/e' ratio of 2.1 following periodontal treatment with the anticipated SD observed in the above‐mentioned study, a two‐sided significance level (α = 0.05) and a dropout rate of 20%, a sample size of 29 in each group would provide 80% detection power as calculated by G*Power (Version 3.01; Win) (Faul, Erdfelder, Lang, & Buchner, 2007).…”
Section: Methodssupporting
confidence: 53%
See 4 more Smart Citations
“…As shown in our recent study on patients with T2DM (Wang et al., 2019), the E/e' ratio in the subjects with no or mild periodontitis and those with severe periodontitis was 8.4 ± 1.7 (standard deviation, SD ) and 10.5 ± 2.9 ( SD ), respectively. Assuming the clinically important reduction in E/e' ratio of 2.1 following periodontal treatment with the anticipated SD observed in the above‐mentioned study, a two‐sided significance level (α = 0.05) and a dropout rate of 20%, a sample size of 29 in each group would provide 80% detection power as calculated by G*Power (Version 3.01; Win) (Faul, Erdfelder, Lang, & Buchner, 2007).…”
Section: Methodssupporting
confidence: 53%
“…On the other hand, LVMI was not altered significantly following the treatment. Our recent study has demonstrated that LVMI is independently correlated with periodontal destruction, rather than the existing periodontal conditions measured by BOP and PD (Wang et al., 2019). Given that the alteration in LV wall thickness is a long process, short‐term control of periodontal inflammation may not necessarily lead to a significant decrease in LV mass.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations